Growth and development simulation model of potato - Soto Garcés, Ana María; Cotes Torres, José Miguel; Rodríguez Caicedo, Daniel (Universidad Pedagógica y Tecnológica de Colombia, 2018)
In order to contribute to the technological development of the potato crop system, the present study was developed with the aim of adapt the supply - demand paradigm to the resource capture processes and allocation of nutrients to simulate the growth and development of the Criolla Colombia variety potato plant. In this paper the process of formulation, parameterization and evaluation of a physiology based demographic model of potato (Solanum phureja) is presented; Two climatic variables were included, the temperature as a thermal time and solar radiation to simulate the photosynthesis, respiration, selective allocation and biomass distribution. The results of the simulation were compared with the independent field data of those used to parameterize the model and found an adequate adjustment in the growth of roots, stems, leaves, stolons and tubers.